2008
DOI: 10.1161/atvbaha.107.160713
|View full text |Cite|
|
Sign up to set email alerts
|

A New Mechanism Involving ERK Contributes to Rosiglitazone Inhibition of Tumor Necrosis Factor-α and Interferon-γ Inflammatory Effects in Human Endothelial Cells

Abstract: Objective-Microvascular endothelium is one of the main targets of the inflammatory response. On specific activation, endothelial cells recruit Th1-lymphocytes at the inflammatory site. We investigated the intracellular signaling mediating tumor necrosis factor (TNF)-␣ and interferon (IFN)-␥ inflammatory response in human microvascular endothelial cells (HMEC-1) and the interfering effects of the peroxisome-proliferator-activated-receptor (PPAR␥) agonist, rosiglitazone (RGZ). Methods and Results-TNF␣ and IFN␥, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
50
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(61 citation statements)
references
References 39 publications
9
50
2
Order By: Relevance
“…This result parallels the effect of TZDs on PTC proliferation, but is opposed to the effect of TZDs on CXCL10 secretion, suggesting that other pathways are involved in the chemokine modulation. Regards MAP-kinase ERK1/2, we were unable to show any significant differences either in the level of ERK1/2 phosphorylation or in the amount of not-phosphorylated protein expression between untreated and treated thyroid cells, in contrast to the results obtained in endothelial cells (Lombardi et al 2008).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This result parallels the effect of TZDs on PTC proliferation, but is opposed to the effect of TZDs on CXCL10 secretion, suggesting that other pathways are involved in the chemokine modulation. Regards MAP-kinase ERK1/2, we were unable to show any significant differences either in the level of ERK1/2 phosphorylation or in the amount of not-phosphorylated protein expression between untreated and treated thyroid cells, in contrast to the results obtained in endothelial cells (Lombardi et al 2008).…”
Section: Discussioncontrasting
confidence: 99%
“…More recently, it has been shown that the TZD effect is not only mediated by activation of the NF-kB and Stat1 classic pathways, but also involves a rapid increase in phosphorylation and activation of ERK1/2 (Lombardi et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Rosiglitazone suppresses TNF-a and IFN-g induced phosphorylation of ERK in human microvascular endothelial cells (14), and ERK is known to be required for the induction of some of the cytokines and chemokines examined in this study (49,50). To determine whether TZDs exert their anti-inflammatory action in HASM cells via the suppression of ERK, we assessed the phosphorylation of ERK in cells stimulated with IL-1b in the presence or absence of TZDs ( Figure 4A).…”
Section: Role Of Erk and Nf-kbmentioning
confidence: 97%
“…However, emerging evidence indicates that this class of drugs also has potent antiinflammatory effects. In vitro, these drugs inhibit the release of various cytokines from activated lymphocytes (12), monocytes (13), endothelial cells (14), microglia, and Phorbol 12-myristate 13-acetate-differentiated THP-1 cells (a human monocytic cell line) (15). In vivo, rosiglitazone and pioglitazone also effectively inhibit airway inflammation in various murine models of asthma (16,17).…”
mentioning
confidence: 99%
“…Total RNA was reverse transcribed using TaqMan RT PCR kit (Applied Biosystems). Gene expression measurement was performed by TaqMan using the 7900HT Sequence Detection Systems (Applied Biosystems, Foster City, CA, USA) as detailed elsewhere (Lombardi et al 2008). Primers/probes for SDHA (Hs00417200_m1), SDHB (Hs01042482_m1), SDHC (Hs01698067_s1), and SDHD (Hs01098144_g1; TaqMan Gene Expression Assays; Applied Biosystems, Warrington, UK) were used.…”
Section: Rna Isolation and Quantitative Real-time Rt-pcrmentioning
confidence: 99%